Coordination chemistry of an amine-substituted bis(pyrazolyl)-pyridine ligand: interaction of a peripheral functional group on a coordination cage with the internal contents of the cavity. Issue 10 (3rd October 2018) - Metherell, Alexander J.; Ward, Michael D.
Abstract: The ligandL an contains two bidentate chelating pyrazolyl-pyridine termini connected to a central aminophenyl ring. In [Ag3 (L an )2 ](ClO4 )3 each ligand coordinates in a pentadentate 2+1+2 manner, connecting all three Ag(I) ions. In contrast, in the octanuclear cubic coordination cage [Co8 (L an )12 ][BF4 ]16 eachL an coordinates as a bis(pyrazolyl-pyridine) tetradentate chelate, with the externally-directed amine groups not coordinated. From its 1 H NMR spectrum this cage has the S 6 symmetric structure containing two fac and six mer tris-chelate Co(II) centres of other octanuclear cages. Slow crystallisation afforded [Co8 (L an )12 Na][BF4 ]17, with S 4 symmetry arising from four fac and four mer tris-chelate Co(II) centres which alternate; the central cavity accommodates an Na + cation and four fluoroborate anions which form a {Na(BF4 )4 } 3– guest. The {Na(BF4 )4 } 3– guest forms FHN hydrogen bonds through the cage windows with exterior amine groups. Rearrangement of the cage structure from S 6 to S 4 symmetry appears to facilitate inclusion of the fourfold symmetric guest. Abstract :